2016
DOI: 10.1016/j.aju.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy free flexible ureteroscopy with holmium: Yttrium-aluminium-garnet laser lithotripsy for removal of renal calculi

Abstract: ObjectiveTo evaluate the feasibility of access sheath insertion and ureteric stent placement without image guidance in flexible ureteroscopic lithotripsy with holmium:yttrium-aluminium-garnet laser for renal stones.Patients and methodsBetween March 2014 and October 2015, 80 patients with renal stones treated with flexible ureteroscopic laser lithotripsy were evaluated. Indications for surgery were renal obstruction, failed shockwave lithotripsy (SWL), stones in polycystic kidneys, and mal-rotated kidneys. A 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
2
9
0
1
Order By: Relevance
“…Studies have confirmed the positive correlation between stone burden and radiation exposure during laser lithotripsy. Hence, clinicians should consider strategies to reduce the total radiation exposure, such as using pulsed instead of continuous fluoroscopy [ 121 ], although there are even defenders of using no fluoroscopy at all [ 122 ].…”
Section: Bibliographic Search Resultsmentioning
confidence: 99%
“…Studies have confirmed the positive correlation between stone burden and radiation exposure during laser lithotripsy. Hence, clinicians should consider strategies to reduce the total radiation exposure, such as using pulsed instead of continuous fluoroscopy [ 121 ], although there are even defenders of using no fluoroscopy at all [ 122 ].…”
Section: Bibliographic Search Resultsmentioning
confidence: 99%
“…Technological advances in flexible URS, such as the ability to get smaller and higher image quality, facilitate navigation of the ureter, renal pelvis, and calyces with excellent visualization and increase the experience of the urologist positively, have made flexible URS safer and more effective, allowing the achievability of radiation-free URS [27] , [32] , [33] , [34] , [35] , [36] . Several studies have demonstrated that reduced radiation and fluoroless protocol during flexible URS can be done safely, including UAS insertion, balloon dilation, and the placement of double-J stents, with no impact on the operation's success, time, or complication rates; thus, this process does not increase technical difficulty [27] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] .…”
Section: Discussionmentioning
confidence: 99%
“…were performed under local anesthesia by urologists. The FURS protocol was standardized to a previous study (11). The stone was positioned in the excretory phase.…”
Section: Surgical Procedure the Methods Of Furs And Furs-musmentioning
confidence: 99%